PERENCANAAN KEUANGAN KELUARGA PADA INDUSTRI RUMAH TANGGA (Indonesian Journal of Social Sciences and Humanities, 2020)
Financial planning is the first step to achieving financial freedom. In the financial sector, humans or people are said to be successful in achieving happiness if they achieve financial freedom. This research is intended for families and each household to be able to make financial plans to achieve prosperity. The problem of lack of support, communication and family motivation as well as the lack of available capital and labor is an obstacle to business continuity in the home industry. The spirit to revive him to continue his business until now has borne fruit out of every decision that is made. Personal financial income and business profitability are getting better every month to continue. Motivation, which is the dominant factor in survival, has influenced the family's financial plans in the home industry. The driving force of experience, financial knowledge and communication with families are the determinants of the success of the intestinal chips home industry in Karang Dima Village, Labuan Badas District, Sumbawa Regency.